2022
DOI: 10.3390/nano12061032
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mini-LEDs with Microlens Arrays and Quantum Dot Film as Extra-Thin, Large-Area, and High-Luminance Backlight

Abstract: The demand for extra-thin, large-area, and high-luminance flat-panel displays continues to grow, especially for portable displays such as gaming laptops and automotive displays. In this paper, we propose a design that includes a light guide layer with a microstructure above the mini-light-emitting diode light board. The light control microstructure of concave parabel-surface microlens arrays on a light-emitting surface increases the likelihood of total internal reflection occurring and improved the uniformity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…[43] Chen et al integrated a microlens array with a brightness enhancement film on an ultra-thin mini-LED; the structure can improve the average luminance as well as the uniformity to 85%. [41] Lai et al demonstrated that the EQE of mini-LEDs can be improved by adopting atomic layer deposition (ALD) sidewall passivation. [44,45] In addition to the abovementioned methods, there are other functional films designed to improve uniformity, such as an advanced diffuser sheet [46] or a translucent layer composed of SiO 2 and TiO 2 .…”
Section: Improvement Of Optical Performancementioning
confidence: 99%
See 4 more Smart Citations
“…[43] Chen et al integrated a microlens array with a brightness enhancement film on an ultra-thin mini-LED; the structure can improve the average luminance as well as the uniformity to 85%. [41] Lai et al demonstrated that the EQE of mini-LEDs can be improved by adopting atomic layer deposition (ALD) sidewall passivation. [44,45] In addition to the abovementioned methods, there are other functional films designed to improve uniformity, such as an advanced diffuser sheet [46] or a translucent layer composed of SiO 2 and TiO 2 .…”
Section: Improvement Of Optical Performancementioning
confidence: 99%
“…Microlens array and brightness enhancement film [41] Spectral dichroic layer [42] Quantum rod enhancement film [43] ALD passivation [44,45] Uniformity Advanced diffuser sheet [46] Microlens array and brightness enhancement film [41] Translucent layer composed of SiO 2 /TiO 2 [47] SiO 2 /graphite bilayered packaging structure [48] Novel direct-lit mini-chip-scale packaged LED [49] Contrast ratio (HDR for AR)…”
Section: Brightnessmentioning
confidence: 99%
See 3 more Smart Citations